Social Network of “Pasar Kaget” Traders in Bintan Regency - Muhammad Aditya; Nanik Rahmawati; Rahma Syafitri (Social Issues Quarterly, 2023)
In Bintan Regency, trading is a common daily activity for many people. Among these traders, there is a social phenomenon known as the "pasar kaget" or "momentary market," where traders only operate during certain times of high crowd attendance or specific events. Pasar kaget traders in Bintan Regency sell various products, including fish balls, sempol, pop ice, Bangkok cashews, balloon toys, and retail goods. This research aims to investigate the social networks within this group of traders. A qualitative descriptive method was employed to analyze social events, phenomena, or conditions, with data collected from 12 traders using a purposive sampling technique. The results indicate that the concept of social capital is applied in the formation of a trader network group, enabling them to carry out trading activities in the pasar kaget. The network of pasar kaget traders also aims to obtain information on events in Bintan Regency and secure facilities or places to trade in the pasar kaget.